Meningeal and cortical grey matter pathology in multiple sclerosis - Gh Popescu, Bogdan F (BioMed Central, 2012)
Although historically considered a disease primarily affecting the white matter of the central nervous system, recent pathological and imaging studies have established that cortical demyelination is common in multiple sclerosis and more extensive than previously appreciated. Subpial, intracortical and leukocortical lesions are the three cortical lesion types described in the cerebral and cerebellar cortices of patients with multiple sclerosis. Cortical demyelination may be the pathological substrate of progression, and an important pathologic correlate of irreversible disability, epilepsy and cognitive impairment. Cortical lesions of chronic progressive multiple sclerosis patients are characterized by a dominant effector cell population of microglia, by the absence of macrophagic and leukocytic inflammatory infiltrates, and may be driven in part by organized meningeal inflammatory infiltrates. Cortical demyelination is also present and common in early MS, is topographically associated with prominent meningeal inflammation and may even precede the appearance of classic white matter plaques in some MS patients. However, the pathology of early cortical lesions is different than that of chronic MS in the sense that early cortical lesions are highly inflammatory, suggesting that neurodegeneration in MS occurs on an inflammatory background and raising interesting questions regarding the role of cortical demyelination and meningeal inflammation in initiating and perpetuating the disease process in early MS.